A Thematic Literature Review on The Impact of Covid-19 Pandemic on Indian Real Estate (Universitas Indonesia, 2022)
The COVID-19 pandemic has impacted the world badly. Almost all activities were suspended, and thus it severely impacted the economy, including the real estate sector. This ongoing pandemic has pushed the sentiments of the sector to their all-time lowest. This research aims to analyze the influence of the COVID-19 pandemic on the real estate industry in India, as well as to determine the most impacted segments. Report achives from eminent property consultants including Knight Frank, Coldwell Banker Richard Ellis (CBRE), and Cushman & Wakefield were reviewed in this study. The qualitative analysis done to the reports and literature shows that both the residential and commercial segments have been impacted badly. However, the residential market has recovered to its pre-COVID level after the first lockdown. Meanwhile, in the case of the commercial market, the pandemic led to many innovations in the office segment, such as hybrid working, portfolio growth, and the hotelization of office spaces. Such innovations were also found in the retail segment, such as reinventing the experience, use of new-age technology, omnichannel strategy, realigning the retail formats, and so forth. Hence, they have boosted these segments and accelerated the recovery. Amongst all the segments, the hospitality segment was the worst-hit segment. It was the first to fall and is last to rise. Due to the fear of getting infected and travel restrictions, tourism has effectively stopped, and this has greatly impacted the hotel segment.